AN OVERVIEW OF ADVANCED 2,2-Diphenyl-1-picrylhydrazyl (DPPH) ANALYSIS TECHNIQUES - Ratnawaty, Gervacia Jenny; Indrawati, Ratih; Wahdaniah, Wahdaniah; Rakhman, Khusna Arif (Walisongo Journal of Chemistry, 2025)
Antioxidants play a crucial role in preventing oxidative damage, necessitating reliable analytical techniques for their evaluation. Oxidative stress, resulting from an imbalance between free radicals and antioxidants in the body, has been associated with various chronic diseases, including cancer, cardiovascular disorders, and neurodegenerative conditions. Therefore, accurately assessing antioxidant activity is essential for developing health-related products and validating their efficacy. This study reviewed and compared various analytical methods used to determine antioxidant activity, emphasizing their advantages, limitations, and applicability across different sample types. Traditional spectrophotometric assays, such as the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, remain widely used because of their simplicity and cost-effectiveness, although they often suffer from matrix interferences. Advanced techniques, including gas chromatography–mass spectrometry (GC–MS), high-performance liquid chromatography coupled with DPPH (HPLCDPPH), electrochemical methods, microfluidic systems, and miniaturized paper-based assays, provide improved sensitivity, accuracy, and efficiency. These methods enable a more comprehensive assessment of antioxidant activity by offering deeper insights into reaction mechanisms and compound interactions. The integration of multiple analytical approaches can further enhance antioxidant characterization, supporting applications in the food, pharmaceutical, and biomedical industries. This review highlights the importance of selecting appropriate analytical techniques based on research objectives and sample characteristics, while also outlining future directions for advancing antioxidant detection methodologies.